BAGAIMANA PENGOPTIMALAN MANAJEMEN ASET DAPAT MENINGKATKAN LABA PERUSAHAAN - Ibnu Aswat; Amanah Hijriah (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2023)
Increasing corporate profits is one of the company's priorities in business operations. Many companies make large sales to increase profits, but the increase in profits does not correspond to forecasts made previously. One of the causes of these charges and expenses is the improper accumulation of depreciation of assets. Many corporate assets have high functional value when asset management is not optimized, but profits are lost due to poor asset management because management cannot control the assets. This has been felt by local businesses in Pontianak City, where efforts have been made to increase profits, starting with service improvements and ending with higher fees, but at the end of the reporting period, the company's earnings report did not meet the expected projections. One of the causes was the high depreciation expense and many assets that were not properly managed, resulting in unnecessary expenses and resulting loss of profits for the company decrease.